Mathematical models of martensitic microstructure - Ball, J (2004)
Martensitic microstructures are studied using variational models based on nonlinear elasticity. Some relevant mathematical tools from nonlinear analysis are described, and applications given to austenite-martensite interfaces and related topics. (C) 2004 Elsevier B.V. All rights reserved.